How safe are over the counter abortion pills-differences between its intended and practical usage and its implications - a study conducted in a tertiary care centre in Shillong, Meghalaya, India - Agarwal, Manika; Datta, Amrita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: MTP Act has been a boon in India with legalization of medical abortion. But its misuse by the rampant usage of over the counter medical abortifacients leads to complications. This study was done to gather data regarding the over the counter purchase and usage of medical abortifacients and its effect on women. Methods: Retrospective analytical study conducted in NEIGRIHMS, Shillong during January-June 2015. Case-sheets of women who had medical abortifacients after purchasing them over the counter were analyzed. Data were obtained under: Age, parity, persons recommending medical abortifacients, gestational age at pill intake, medicines taken, patients taking medicines more than once in same pregnancy, interval between pill intake and hospital presentation, presenting complaints, co-morbidities, outcome following self-administration of medical abortifacients and management given. Data were tabulated, calculated. Results: Out of 30 cases, primis were majority (33.33%). Maximum pills popped on pharmacist’s (73.33%) recommendations. 76.66% of patients took the pills within 63 days of gestation. 30% could not recall their medicines and 23% took I-pills as abortifacients. 23.33% took repeat dose in same pregnancy. 43.33% presented within 5-10 days of pill intake. Commonest presentation was irregular bleed and passage of fleshy mass with bleeding PV, 33.33%. Anaemia was the commonest co-morbidity (76.66%). Retained products were in 56.66%. 70% managed by surgical evacuation alone, with blood transfusion in 10% of patients. Conclusions: Over the counter purchase of medical abortifacients without proper knowledge causes unprecedented maternal morbidity and mortality. National bodies should impose strict legislations to stop this.